ANALYSIS OF THE INFLUENCE OF WORK FROM HOME WORK SYSTEMS AND WORK MOTIVATION ON EMPLOYEE WORKLIFE BALANCE DURING THE COVID-19 PANDEMIC (CASE STUDY AT PT ASURANSI SINARMAS MSIG TBK) - Megawati Megawati; Okder Pendrian (Jurnal Scientia, 2023)
This study aims to determine the effect of the Work from Home work system and Work Motivation on the Worklife Balance of employees of PT Asuransi Sinarmas MSIG Tbk . This study uses a quantitative approach with multiple linear regression analysis methods and processed with Smart Partial Least Square. Determination of the sample for this study as many as 89 respondents. The results of this study indicate that the variable work system work from home has a positive influence on the work life balance of employees. The work motivation variable has no positive effect on work life balance, while the work system variable has a positive effect on work motivation, as well as the work system variable and work motivation have a positive effect on the work life balance of employees of PT Asuransi Sinarmas MSIG Tbk simultaneously